2011
DOI: 10.1038/cdd.2010.188
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-ΔNp63α is a key regulator of the cisplatin-induced microRNAome in cancer cells

Abstract: Head and neck squamous cell carcinoma (HNSCC) cells exposed to cisplatin (CIS) displayed a dramatic ATM-dependent phosphorylation of DNp63a that leads to the transcriptional regulation of downstream mRNAs. Here, we report that phospho (p)-DNp63a transcriptionally deregulates miRNA expression after CIS treatment. Several p-DNp63a-dependent microRNA species (miRNAs) were deregulated in HNSCC cells upon CIS exposure, including miR-181a, miR-519a, and miR-374a (downregulated) and miR-630 (upregulated). Deregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 41 publications
6
154
1
Order By: Relevance
“…36 We have further showed that the specific microRNAs downregulated or upregulated in SCC cells in response to cisplatin treatment are involved in a broad plethora of cellular processes, including apoptosis, autophagy, and various metabolic and signaling pathways. 36-39 P-ΔNp63α was also shown to transcriptionally activate or repress the specific microRNA promoters depending on the chromatin components bound to this transcriptional factor in SCC cells upon cisplatin exposure. 28 In this report, we continue our quest to understand the role of the cisplatin-induced TP63-regulated microRNAs in epigenetic regulation and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 We have further showed that the specific microRNAs downregulated or upregulated in SCC cells in response to cisplatin treatment are involved in a broad plethora of cellular processes, including apoptosis, autophagy, and various metabolic and signaling pathways. 36-39 P-ΔNp63α was also shown to transcriptionally activate or repress the specific microRNA promoters depending on the chromatin components bound to this transcriptional factor in SCC cells upon cisplatin exposure. 28 In this report, we continue our quest to understand the role of the cisplatin-induced TP63-regulated microRNAs in epigenetic regulation and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…34 We have also shown that the phosphorylated (p)-ΔNp63α protein is critical for the transcriptional regulation of downstream mRNAs and microRNAs in SCC cells upon cisplatin exposure. 35,36 Moreover, we have reported that p-ΔNp63α regulates microRNA expression in cisplatin-treated SCC cells through both transcriptional and post-transcriptional mechanisms. 36 We have further showed that the specific microRNAs downregulated or upregulated in SCC cells in response to cisplatin treatment are involved in a broad plethora of cellular processes, including apoptosis, autophagy, and various metabolic and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies revealed that miR-519A was downregulated by ΔNp63α in cancers (48), and overexpression of ΔNp63α was beneficial for HNSCC resistance to chemotherapy-induced cell death via inhibiting the transcription of TAp73b (49). One study found that the downregulation of ΔNp63α was a determinant of cellular response to DNA damage in HNSCC (50).…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] In SCC cells, cisplatin exposure phosphorylates ΔNp63α, which directly regulates the transcription of many miRNAs. 44 Among the direct targets, miR-181a, miR-519a, miR-374a and miR-630 has been shown to regulate autophagy-related proteins, 34 which suggests that miRNAs can modulate autophagy pathway at another translational level. A number of previous studies have reported the direct involvement of p53 in autophagy.…”
Section: Mirna: the Third Dimension Of P53-mediated Autophagymentioning
confidence: 99%